2021
DOI: 10.1038/s41467-021-21960-4
|View full text |Cite
|
Sign up to set email alerts
|

Citrullination of pyruvate kinase M2 by PADI1 and PADI3 regulates glycolysis and cancer cell proliferation

Abstract: Chromodomain helicase DNA binding protein 4 (CHD4) is an ATPase subunit of the Nucleosome Remodelling and Deacetylation (NuRD) complex that regulates gene expression. CHD4 is essential for growth of multiple patient derived melanoma xenografts and for breast cancer. Here we show that CHD4 regulates expression of PADI1 (Protein Arginine Deiminase 1) and PADI3 in multiple cancer cell types modulating citrullination of arginine residues of the allosterically-regulated glycolytic enzyme pyruvate kinase M2 (PKM2). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…To refine our search space, we collated 69 previously published ChIP-seq and ATAC-seq datasets that were specifically performed on melanoma or melanocyte samples 18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] (Supplemental Table 1). We reasoned these regions of the genome are more likely to bind transcription/chromatin factors and refer to them as putative melanoma regulatory regions (pMRRs).…”
Section: Putative Regulatory Regions In Melanoma Are Enriched For Hot...mentioning
confidence: 99%
“…To refine our search space, we collated 69 previously published ChIP-seq and ATAC-seq datasets that were specifically performed on melanoma or melanocyte samples 18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] (Supplemental Table 1). We reasoned these regions of the genome are more likely to bind transcription/chromatin factors and refer to them as putative melanoma regulatory regions (pMRRs).…”
Section: Putative Regulatory Regions In Melanoma Are Enriched For Hot...mentioning
confidence: 99%
“…However, few HRG related studies were found in OSCC. The PADI3 has anticancer effect through the arresting of cell cycle in colon cancer, and it regulates the glycolysis in multiple cancer cell types [ 44 ]. The MIPOL1 may induce tumor suppression in nasopharyngeal carcinoma resulting anticancer effect [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study published last year showed that PADI1- and PADI3-mediated citrullination of the glycolytic enzyme pyruvate kinase M2 (PKM2) alters its binding to amino acids and promotes glycolysis in cancer cells [ 96 ]. A more recent study showed that citrullination of glukokinase leads to reduction of its catalytic activity and results in reduced insulin secretion in response to glucose stimulation [ 97 ].…”
Section: Molecular and Cellular Functions Regulated By Citrullination...mentioning
confidence: 99%